Antara Partisipasi dan Mobilisasi: Dinamika Perilaku Politik Masyarakat dalam Pilkada Donggala 2024 - Abdul Kadir Patta; Muhammad Nur Ali; Syufri Syufri; Alimuddin Alimuddin; Hajir Bahrun Maula; Wahyu Wiranto (Jurnal Civic Hukum, 2026)
This study examines the dynamics of community political behavior between participation and mobilization in the 2024 Donggala Regency Regional Head Election (Pilkada). Political participation is an important indicator of the quality of democracy, as it reflects the level of citizen awareness and involvement in the political process. This study aims to analyze the level of community political participation and identify factors influencing it. This study uses a mixed methods approach with a dominant qualitative approach, data collection techniques through in-depth interviews, observation, and documentation studies. Data analysis was carried out interpretively with an interactive analysis model, and validity was tested through triangulation. The results show that the level of community political participation in Donggala Regency is relatively high at 71,3%, but this participation tends to be mobilization and transactional. Dominant factors influencing community participation include the practice of money politics, the influence of local elites, and social encouragement from family and community leaders. In addition, women's participation is higher than men's, indicating an increase in inclusiveness in local democracy. However, community involvement is still driven more by pragmatic factors than rational political awareness. These findings indicate that the quality of political participation in Donggala Regency still faces challenges, particularly in fostering participation based on democratic awareness. Therefore, strengthening political education and improving election governance are necessary to enhance the quality of public participation.